UK national clinical audit: management of pregnancies in women with HIV. Issue 1 (December 2017) - Raffe, S.; Curtis, H.; Tookey, P.; Peters, H.; Freedman, A.; Gilleece, Y.
Abstract Background The potential for HIV transmission between a pregnant woman and her unborn child was first recognized in 1982. Since then a complex package of measures to reduce risk has been developed. This project aims to review UK management of HIV in pregnancy as part of the British HIV Association (BHIVA) audit programme. Methods The National Study of HIV in Pregnancy and Childhood (NSHPC), a population-based surveillance study, provided data for pregnancies with an expected delivery date from 1/1/13 - 30/6/14. Services also completed a survey on local management policies. Data were audited against the 2012 BHIVA pregnancy guidelines. Results During the audit period 1483 pregnancies were reported and 112 services completed the survey. Use of dedicated multidisciplinary teams was reported by 99% although 26% included neither a specialist midwife nor nurse. 17% of services reported delays >1 week for HIV specialist review of women diagnosed antenatally. Problematic urgent HIV testing had been experienced by 9% of services although in a further 49% the need for urgent testing had not arisen. Delays of >2 h in obtaining urgent results were common. Antiretroviral therapy (ART) was started during pregnancy in 37% women with >94% regimens in accordance with guidelines. Late ART initiation was common, particularly in those with a low CD4 count or high viral load. Eleven percent of services reported local policy contrary to guidelines regarding delivery mode for women with a VL <50 copies/mL at ≥36 weeks. According to NSHPC reports 27% of women virologically eligible for vaginal delivery planned to deliver by CS. Conclusions Pregnant women in the UK are managed largely in accordance with BHIVA guidelines. Improvements are needed to ensure timely referral and ART initiation to ensure the best possible outcomes.